The Effect of Operating Cash Flows and Book Tax Differences on Profit Growth in Large Trading and Small Trading Sub-Sector Companies Listed on the Indonesia Stock Exchange - Cindy Ramli (Outline Publisher, 2022)
This study aims to determine the effect of operating cash flow and book tax difference on profit growth in large and small trading sub-sector companies listed on the Indonesia Stock Exchange. The research methodology used is a quantitative descriptive method. The population in this study are large and small trading sub-sector companies totaling 61 companies. The results of the research analysis show that operating cash flow has no significant effect on profit growth in large trading and small trading sub-sector companies based on the results of partial hypothesis testing. The results of the research analysis show that Book Tax Difference has a significant effect on Profit Growth in Large Trading and Small Trade Sub-Sector Companies based on the results of partial hypothesis testing. The results of the research analysis show that Operating Cash Flow and Book Tax Difference have a significant effect on Profit Growth in Large Trading and Small Trading Subsector Companies based on the results of simultaneous hypothesis testing.